Whole-body biomechanical load in running-based sports: The validity of estimating ground reaction forces from segmental accelerations - Verheul, J.; Gregson, W.; Lisboa, P.; Vanrenterghem, J.; Robinson, M. A. (Journal of Science and Medicine in Sport, 2019)
Objectives: Unlike physiological loads, the biomechanical loads of training in running-based sports are still largely unexplored. This study, therefore, aimed to assess the validity of estimating ground reaction forces (GRF), as a measure of external whole-body biomechanical loading, from segmental accelerations. Methods: Fifteen team-sport athletes performed accelerations, decelerations, 90° cuts and straight running at different speeds including sprinting. Full-body kinematics and GRF were recorded with a three-dimensional motion capture system and a single force platform respectively. GRF profiles were estimated as the sum of the product of all fifteen segmental masses and accelerations, or a reduced number of segments. Results: Errors for GRF profiles estimated from fifteen segmental accelerations were low (1-2 N/kg) for low-speed running, moderate (2-3 N/kg) for accelerations, 90° cuts and moderate-speed running, but very high (>4 N/kg) for decelerations and high-speed running. Similarly, impulse (2.3-11.1%), impact peak (9.2-28.5%) and loading rate (20.1-42.8%) errors varied across tasks. Moreover, mean errors increased from 3.26 ± 1.72 N/kg to 6.76 ± 3.62 N/kg across tasks when the number of segments was reduced. Conclusions: Accuracy of estimated GRF profiles and loading characteristics was dependent on task, and errors substantially increased when the number of segments was reduced. Using a direct mechanical approach to estimate GRF from segmental accelerations is thus unlikely to be a valid method to assess whole-body biomechanical loading across different dynamic and high-intensity activities. Researchers and practitioners should, therefore, be very cautious when interpreting accelerations from one or several segments, as these are unlikely to accurately represent external whole-body biomechanical loads.